Minocycline-Derived Silver Nanoparticles for Assessment of Their Antidiabetic Potential against Alloxan-Induced Diabetic Mice - Syed Akif Raza Kazmi; Muhammad Zahid Qureshi; Sadia; Saleh S. Alhewairini; Shaukat Ali; Shazia Khurshid; Muhammad Saeed; Shumaila Mumtaz; Tafail Akbar Mughal (Pharmaceutics, 2021)
Diabetes is a life-threatening disease, and chronic diabetes affects parts of the body including the liver, kidney, and pancreas. The root cause of diabetes is mainly associated with oxidative stress produced by reactive oxygen species. Minocycline is a drug with a multi-substituted phenol ring and has shown excellent antioxidant activities. The objective of the present study was to investigate the antidiabetic potential of minocycline-modified silver nanoparticles (mino/AgNPs) against alloxan-induced diabetic mice. The mino/AgNPs were synthesized using minocycline as reducing and stabilizing agents. UV-visible, FT-IR, X-ray diffraction (XRD), and transmission electron microscopy (TEM) were applied for the characterization of mino/AgNPs. A 2,2-diphenyl-1-picrylhydrazyl free radical scavenging assay was conducted to determine the antioxidant potential of newly synthesized mino/AgNPs. The results revealed that the mino/AgNPs showed higher radical scavenging activity (IC50 = 19.7 µg/mL) compared to the minocycline (IC50 = 26.0 µg/mL) and ascorbic acid (IC50 = 25.2 µg/mL). Further, mino/AgNPs were successfully employed to examine their antidiabetic potential against alloxan-induced diabetic mice. Hematological results showed that the mice treated with mino/AgNPs demonstrated a significant decrease in fasting blood glucose level and lipid profile compared to the untreated diabetic group. A histopathological examination confirmed that the diabetic mice treated with mino/AgNPs showed significant recovery and revival of the histo-morphology of the kidney, central vein of the liver, and islet cells of the pancreas compared to the untreated diabetic mice. Hence, mino/AgNPs have good antidiabetic potential and could be an appropriate nanomedicine to prevent the development of diabetes.